Efficacy and safety of abrocitinib for moderate-to-severe atopic dermatitis in adolescents and adults: Meta-analysis - Li, Ling; Yu, Jiajun; Chen, Baoqing; Guo, Ying; Yang, Yufeng (Frontiers in Pharmacology, 2023)
Objective: This study aims to investigate the safety and efficacy of abrocitinib in treating moderate-to-severe AD in adolescents and adults. Methods: Pubmed, Cochrane, Embase, and Web of science data base were searched from inception to 9 August 2022. All randomized controlled trials (RCTs) evaluating the efficacy and safety of abrocitinib in moderate to severe AD were included in the meta-analysis. Results: This meta-analysis comprised 7 studies and found that 100 mg or 200 mg of abrocitinib significantly improved IGA [RR = 2.44, 95% CI (1.93–3.08)] [RR = 3.16, 95% CI (2.52–3.96)] and EASI-75[RR = 2.18, 95%CI (1.78–2.67)] [RR = 3.04, 95%CI (2.22–4.16)] responses compared to placebo. Following that, the population was divided into adolescent and adult groups. The abrocitinib improved IGA, EASI-75 responses, and it was still superior to placebo in both the adolescent and the adult groups. PP-NRS4 response index demonstrated that abrocitinib had a greater effect than placebo at 100 mg [RR = 2.22, 95% CI 1.80–2.72] and 200 mg [RR = 3.28, 95% CI 2.59–4.17]. Abrocitinib improved PSAAD, POEM, DLQI, CDLQI, and HADS more than a placebo. Conclusion: In conclusion, this meta-analysis preliminarily demonstrated that abrocitinib had higher efficacy and safety in the treatment of moderate-to-severe AD in adolescents and adults. In addition, abrocitinib could rapidly relieve itching, and effectively improve symptoms and signs, with a greater effect at the dosage of 200 mg than 100 mg.